International Architecture News (project baikal, 2025)
The news section presents the winners of the competition organised by the UIA in collaboration with UNESCO to empower the next generation in participatory urban design. It also announces the 7th Baku International Architecture Award.
Keywords: UIA; UNESCO; participatory design; Baku International Architecture Award